The Role of Chef in Improving Hygiene and Sanitation in Food Preparation at Eastin Ashta Resort Canggu - Putri , Ida Ayu Karina; Arini , Ni Nyoman; Putra, I Made Perdi Permana (LPPM Universitas Dhyana Pura, 2026)
The hotel kitchen is a critical operational area where hygiene and sanitation practices directly determine food quality and guest safety. This study aims to analyze the role of the chef in improving hygiene and sanitation during food preparation at Eastin Ashta Resort Canggu, identify the challenges encountered, and describe the efforts made to overcome them. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews with the Executive Chef and Chef de Partie, and documentation. The results reveal that the chef plays a central role in supervising staff personal hygiene, kitchen area cleanliness, equipment sanitation, ingredient control, and conducting regular briefings and training. Challenges identified include inconsistent staff discipline in following Standard Operating Procedures (SOP), high-intensity peak hour operations, limited supervision time, drainage blockage from food residue, and varying work habits among staff. To address these challenges, the chef implements pre-operational briefings, routine monitoring, cleanliness schedules, periodic food safety training, and SOP evaluations. The study concludes that the chef's active leadership in operational, supervisory, and evaluative functions is essential for maintaining consistent hygiene and sanitation standards, thereby supporting food safety, service quality, and the hotel's professional reputation.